2017
DOI: 10.1002/ange.201705569
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinspired, Size‐Tunable Self‐Assembly of Polymer–Lipid Bilayer Nanodiscs

Abstract: Polymer-based nanodiscs are valuable tools in biomedical researcht hat can offer ad etergent-free solubilization of membrane proteins maintaining their native lipid environment. Herein, we introduce anovel ca. 1.6 kDa SMAbased polymer with styrene:maleic acid moieties that can form nanodiscs containing aplanar lipid bilayer whichare useful to reconstitute membrane proteins for structural and functional studies.The physicochemical properties and the mechanism of formation of polymer-based nanodiscs are characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

7
2

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 38 publications
1
73
1
Order By: Relevance
“…Following the initial incorporation of PagP and bacteriorhodopsin into SMA nanodiscs (11), a variety of membrane proteins have been studied using similar preparations (12,15,16). Further development has led to similar polymers with greater pH stability and decreased susceptibility to divalent metal cations, among other favorable properties (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Following the initial incorporation of PagP and bacteriorhodopsin into SMA nanodiscs (11), a variety of membrane proteins have been studied using similar preparations (12,15,16). Further development has led to similar polymers with greater pH stability and decreased susceptibility to divalent metal cations, among other favorable properties (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…These results suggest that macro-nanodiscs possess a negative magnetic susceptibility and align in such a way that the lipid bilayer normal orients perpendicular to the magnetic field direction as shown in previous studies. 40,43,47 The magnetic susceptibility of these nanodiscs can be changed by the addition of paramagnetic metal ions such as YbCl3 which has a positive magnetic susceptibility. [48][49] To study the alignment behavior of macro-nanodiscs 31 P NMR spectra were acquired as a function of time by adding different concentrations of YbCl3 to the aligned macro-nanodiscs.…”
Section: Resultsmentioning
confidence: 99%
“…The martini DLPC lipid was chosen for our study as it provide a general phosphatidylcholine lipid and correspond to atomistic C12:0 dilauroyl (DLPC)-C14:0 dimyristoyl (DMPC) tails. In our previous experimental study, 1,2 we demonstrated the spontaneous lipid-nanodisc formation by both polymers selectively for phosphatidylcholine lipid with C14 tails. The DLPC lipid-bilayer was built using Martini insane python program and simulated for 2 µs prior to SMA-EA.…”
Section: Simulationmentioning
confidence: 90%